PENGARUH PROFITABILITAS DAN NILAI PASAR TERHADAP HARGA SAHAM PADA PT SUMBER ALFARIA TRIJAYA Tbk PERIODE 2013 - 2023 - Ikbal Suhendra; Enny Savitri (Journal of Research and Publication Innovation, 2025)
This study aims to determine the effect of Profitability and Market Value on Share Price at PT Sumber Alfaria Trijaya Tbk for the Period 2013 - 2023. The type of research used is descriptive quantitative. The data analysis methods used include: Descriptive Statistics, Classical Assumption Test (Normality, Multicolonierity, Hesteroscedasticity, Autocolleration), Multiple Regression Test, Hepotesis Test (partial T Test and simultaneous F Test), Determination Coefficient Test (R2). The results of this study indicate that Profitability proxied by Return On Equity has a negative and significant effect on Stock Prices at PT Sumber Alfaria Trijaya Tbk, this is evidenced by tcount = -2.038 < ttable = 2.262 with a significant value of 0.076 > 0.05. Market Value proxied by Earning Per Share has a positive and significant effect on Stock Price at PT Sumber Alfaria Trijaya Tbk, this is evidenced by the tcount of 9.885> ttable 2.262 with a significant value of 0.000 <0.05. Return On Equity and Earning Per Share simultaneously have a positive and significant effect on Stock Price at PT Sumber Alfaria Trijaya Tbk, this is evidenced by Fcount = 78.519 > Ftable = 4.459 with a significant value of 0.000 <0.05.